Pelatihan Pembuatan Lilin Aromaterapi Limbah Minyak Jelantah Ibu-Ibu PKK Desa Karanganyar, Kabupaten Pemalang - Tiara Dwi Wulandari; Prasetyo Listiaji (Universitas Negeri Semarang, 2024)
Environmental damage is often found to be a global issue today. One of the causes of ecological problems is the use of cooking oil. Used cooking oil is oil that is repeatedly used and no longer used. The negative impact if used cooking oil is thrown directly into the environment without processing it first is very large, such as environmental pollution, thereby damaging the aquatic ecosystem. However, public awareness about managing this waste still needs to be improved. This community service activity aims to increase public knowledge of the impact of using and disposing of used cooking oil on body health and the environment and provide education regarding making aromatherapy candles using used cooking oil waste. This community service activity was carried out on August 1, 2023, at Karanganyar Village Hall, Bantarbolang District, Pemalang Regency. PKK women attended this activity in 6 hamlets in Karanganyar Village. Educational activities include presenting material to service providers and practicing making aromatherapy candles from used cooking oil. As a result of this service, all participants understand the negative impacts of used cooking oil that need to be avoided and how to process used cooking oil into aromatherapy candles. Some participants were even interested in making the product an independent business.